What happened in the South American Gran Chaco? Diversification of the endemic frog genus Lepidobatrachus Budgett, 1899 (Anura: Ceratophryidae) - Brusquetti, Francisco; Netto, Flavia; Baldo, Diego; Haddad, Celio F. B. [UNESP] (Elsevier B.V., 2018)
The Chaco is one the most neglected and least studied regions of the world. This highly-seasonal semiarid biome is an extensive continuous plain without any geographic barrier, and in spite of its high species diversity, the events and processes responsible have never been assessed. Miocene marine introgressions and Pleistocene glaciations have been mentioned as putative drivers of diversification for some groups of vertebrates in adjacent biomes of southern South America. Here we used multilocus data (one mitochondrial and six nuclear loci) from the three species of the endemic frog genus Lepidobatrachus (Lepidobatrachus asper, Lepidobatrachus laevis, and Lepidobatrachus llanensis) to determine if any of the historical events suggested as drivers of vertebrate diversification in southern South America are related to the diversification of the genus and if the Chaco is indeed a biome without barriers. Using fossil calibration in a coalescent framework we estimated that the genus diversified in the second half of the Miocene, coinciding with marine introgressions. Genetic patterns and historical demography suggest an important role of old archs and cratons as refuges during floods. In one species of the genus, L. llanensis, genetic structure reveals some breaks along the landscape, the main one of which corresponds to an area of the central Chaco that may act as a climatic barrier. Additionally, we found differential effects of the main Chacoan rivers on species of Lepidobatrachus that could be related to the time of persistence of populations in the areas influenced by these rivers.
Keywords: Miocene marine introgression; Species tree; Fossil calibration; Lepidobatrachus asper; Lepidobatrachus laevis; Lepidobatrachus llanensis